2016
DOI: 10.1017/s1466252316000104
|View full text |Cite
|
Sign up to set email alerts
|

Where literature is scarce: observations and lessons learnt from four systematic reviews of zoonoses in African countries

Abstract: The success of a systematic review depends on the availability, accessibility and quality of literature related to the review question. This paper presents the literature found in four systematic reviews conducted for a selection of zoonotic hazards in four livestock value chains in Africa, as well as setting out the challenges in conducting the reviews. The protocol was designed following international standards, and addressed four questions around prevalence, risk factors, control options and impact of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 31 publications
(32 reference statements)
0
38
0
Order By: Relevance
“…In one workshop, a supervisor maintained that he had no problem with students paying others to write their theses for them, since that was the way scientists published papers, which sparked a debate on the ethical aspects of having publications written by paid authors that are not on the author list. The questions on which paper to cite also served a good purpose to start the discussion about what to do when publications are behind pay walls, which can create problems, particularly for researchers in low-income countries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one workshop, a supervisor maintained that he had no problem with students paying others to write their theses for them, since that was the way scientists published papers, which sparked a debate on the ethical aspects of having publications written by paid authors that are not on the author list. The questions on which paper to cite also served a good purpose to start the discussion about what to do when publications are behind pay walls, which can create problems, particularly for researchers in low-income countries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies on rural livestock-keeping communities in Africa have focused their research on zoonotic diseases, 12 with minimal attention paid to work practice-related risks. An exception to this is a 2-part review of the occupational risks of livestock and crop farmers in The Gambia by Kuye et al 13,14 In their report, 80% of farmers reported a work-related injury in the past year, which was far higher than our results.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to conclude if this discordance can be explained by questionnaire structure, by biases in 1 or both studies, or by differences between Gambian and Ugandan farmers. [12][13][14] To our knowledge, there have been no previous efforts to describe the frequency with which livestock-associated tasks are performed in this setting, though limited prior efforts have been made to describe the delegation of livestockassociated tasks within households in rural African communities. A review of literature from Zimbabwe found that men are usually responsible for outside work and women are responsible for inside work and the feeding of animals; domestic fowl are mainly owned by women and boys are responsible for milking and herding animals.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, abstracts and full papers, when available, were then reviewed, and data were extracted from all papers and abstracts fulfilling the inclusion criteria listed above. This study used the criteria for poor quality as reported by Alonso et al (2016), in short, poor quality was defined as methods not clear or incomplete, inappropriate methods or data analyses, biased or potentially biased selection that is not acknowledged, and reported results that are incomplete, unclear, or inaccurate.…”
Section: Methodsmentioning
confidence: 99%